Manton Marble papers - Marble, Manton, 1834-1917.
Correspondence, telegrams, articles, drafts of Democratic Party policy statements, financial records, photographs, and other papers chiefly relating to Marble's career as editor and owner of the New York World and to his role in New York State and national Democratic Party politics in the period between the beginning of the Civil War and the close of the 19th century. Includes a draft of the "Peace Plank" of the Democratic platform of 1864. Subjects include the presidential election of 1876, silver question, and Marble's efforts on behalf of bimetallism in the U.S. and his mission to Europe in 1885 as President Grover Cleveland's representative to consult with European governments on the subject. Also includes documents relating to the shutdown of the World in 1864 by the Abraham Lincoln administration.
Correspondents include Samuel Greene Arnold, Samuel L.M. Barlow, Thomas F. Bayard, August Belmont, W.H. Bogart, Calvert Comstock, Samuel Sullivan Cox, David G. Croly, George Ticknor Curtis, Charles A. Dana, James R. Doolittle, John Fiske, William Henry Hurlbert, Reverdy Johnson, Michael C. Kerr, Joseph Medill, Fitz-John Porter, John Finley Rathbone, Horatio Seymour, Herbert Spencer, Richard Henry Stoddard, Samuel J. Tilden, Clement L. Vallandigham, Henry Watterson, and Horace White.
Editor and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arnold, Samuel Greene, -- 1821-1880 -- Correspondence; Barlow, Samuel L. M. -- 1826-1889 -- Correspondence; Bayard, Thomas F. -- 1828-1898 -- Correspondence; Belmont, August, -- 1816-1890 -- Correspondence; Bogart, W. H. -- 1810-1888 -- Correspondence; Cleveland, Grover, -- 1837-1908.; Comstock, Calvert, -- 1812-1876 -- Correspondence; Cox, Samuel Sullivan, -- 1824-1889 -- Correspondence; Croly, David G. -- 1829-1889 -- Correspondence; Curtis, George Ticknor, -- 1812-1894 -- Correspondence; Dana, Charles A. -- 1819-1897 -- Correspondence; Doolittle, James R. -- 1815-1897 -- Correspondence; Fiske, John, -- 1842-1901 -- Correspondence; Hurlbert, William Henry, -- 1827-1895 -- Correspondence; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Kerr, Michael C. -- 1827-1876 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Medill, Joseph, -- 1823-1899 -- Correspondence; Porter, Fitz-John, -- 1822-1901 -- Correspondence; Rathbone, John Finley, -- 1819- -- Correspondence; Seymour, Horatio, -- 1810-1886 -- Correspondence; Spencer, Herbert, -- 1820-1903 -- Correspondence; Stoddard, Richard Henry, -- 1825-1903 -- Correspondence; Tilden, Samuel J. -- 1814-1886 -- Correspondence; Vallandigham, Clement L. -- 1820-1871 -- Correspondence; Watterson, Henry, -- 1840-1921 -- Correspondence; White, Horace, -- 1834-1916 -- Correspondence; Democratic Party (N.Y.); Democratic Party (U.S.); World (New York, N.Y. : 1860-1931); American newspapers -- New York (State) -- New York; Bimetallism; Elections -- United States -- 1864.; Elections -- United States -- 1876.; Silver question; Europe -- Foreign relations -- United States; New York (State) -- Politics and government; United States -- Foreign relations -- Europe; United States -- History -- Civil War, 1861-1865 -- Censorship; United States -- Politics and government -- 1861-1865.; United States -- Politics and government -- 1865-1900.; Editors; Publishers